2010
DOI: 10.1124/mol.110.066084
|View full text |Cite
|
Sign up to set email alerts
|

Arg13 of B-Type Natriuretic Peptide Reciprocally Modulates Binding to Guanylyl Cyclase but Not Clearance Receptors

Abstract: B-type natriuretic peptide (BNP) decreases cardiac preload and hypertrophy. As such, synthetic BNP, nesiritide, was approved for the treatment of acutely decompensated heart failure. However, two problems limit its therapeutic potential. First, ensuing hypertension decreases urine output, and second, guanylyl cyclase-A (GC-A), the primary signaling receptor for BNP, is down-regulated in heart failure. Thus, alternative or chimeric natriuretic peptides maintaining the renal but lacking the vasorelaxation proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These intracellular cGMP measurements have limited accuracy, precision and reproducibility. They are tedious with the preparation of cell lysate and depend on standard curve by radioimmunoassays [ 206 ]. One stable cell-based assay is based on the NPR-A in HEK 293 cell.…”
Section: Diagnostic Valuesmentioning
confidence: 99%
“…These intracellular cGMP measurements have limited accuracy, precision and reproducibility. They are tedious with the preparation of cell lysate and depend on standard curve by radioimmunoassays [ 206 ]. One stable cell-based assay is based on the NPR-A in HEK 293 cell.…”
Section: Diagnostic Valuesmentioning
confidence: 99%
“…Phosphorylation is required for peptide activation, and prolonged natriuretic peptide exposure or acute exposure to phorbol esters or calcium-elevating agents causes receptor dephosphorylation and inactivation (10).…”
Section: Natriuretic Peptides and Atp Activate And Gö6976 Inhibits Gumentioning
confidence: 99%
“…Furthermore, data generated from these aforementioned systems are limited in terms of reproducibility, precision and accuracy in addition to appropriate comparison with the traditional RAST. The disadvantages associated with these assays prompted us to develop a stable cell-based assay for the potency determination of therapeutic rhBNP, based on studies on GC-A receptor using HEK293 cells [32] . There are several advantages in our assay: 1) a single high-responsiveness clone was isolated with stability confirmed even a in culture for 65 passages; 2) the operation is drastically simplified with detection of cGMP in culture supernatants and use of non-radioactive materials in immunoassays in a high through-put manner; 3) the new assay has demonstrated defined specificity, greater precision and reproducibility in validation studies compared with RAST, for which no previous studies have reported.…”
Section: Discussionmentioning
confidence: 99%